Mismatch Between Linguistic Structure and Facts: An Analysis of State Officials’ Statements Based on Stuart Hall’s Theory of Representation - Rai Bagus Triadi; Diyah Iis Andriani (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2026)
The phenomenon of public distrust toward state officials is not solely caused by a mismatch between language and empirical reality, but also by the complex processes through which meaning is represented within the social sphere. This study aims to analyze how state officials’ language constructs, reproduce, and distort reality through the lens of Stuart Hall’s theory of representation. Within this framework, language is understood not merely as a reflection of reality, but as a practice that actively produces meaning through systems of signs and discourse. This research employs a qualitative approach, using discourse analysis, to examine statements made by state officials in the public domain. The findings indicate that meaning within officials’ statements is dynamic and open to multiple interpretations, shaped by social context, ideology, and the positionality of the audience. Public distrust emerges from the gap between meanings encoded by officials (encoding) and those interpreted by the public (decoding), including oppositional readings. The expansion of access to information and digital literacy has strengthened the role of the public as active agents in producing and disseminating meaning, thereby diminishing officials’ exclusive control over representation. The illogicality and inconsistency found in certain statements reflect not only cognitive limitations but also a failure to construct representations aligned with the collective experiences of society. Therefore, public trust is largely determined by the success of the representational process, encompassing the construction of meaning, strategies of message encoding, and the dynamics of audience interpretation within broader social contexts.